Study on the regulation of focal adesions and cortical actin by matrix nanotopography in 3D environment - Han, Jingjing (2020)
Matrix nanotopography plays an important role in regulating cell behaviors by providing spatial as well as mechanical cues for cells to sense. It has been proposed that nanoscale topography is possible to modulate the tensions which direct the formation of cytoskeleton and the organization of the membrane receptor within the cell, which in turn regulate intracellular mechanical and biochemical signaling. With current studies on this topic being performed mainly in 2D platforms, the question on how nanotopography can influence cell bahaviors in 3D environments has yet to be addressed. In this paper, we explored this question by placing cells in 3D hollow spherical polydimethylsiloxane scaffolds. After culturing rat embryonic fibroblast cells in two kinds of scaffold, one with smooth surface and the other with numerous nano-spikes, we observed that cells in the smooth scaffold have more anchoring sites and more focal adhesions than in the etched scaffold. Moreover, we found the presence of correlation between cortical actin, the important component for supporting cell attachment, and local cell geometry.